A Framework Approach for Risk Assessment and Management of CO2 Geological Storage - Pontes, Talita; Peyerl, Drielli; Moretto, Evandro (International Journal of Advanced Engineering Research and Science, 2021)
The aim of this article is to analyze the particular contributions provided by the Risk Assessment and Management framework to the CO2 geological storage process on the offshore oil and gas sector. The CO2 geological storage, inherent to Carbon Capture and Storage (CCS) activities, is characterized as an effective mitigation option to reduce the levels of this gas in the environment. The risk assessment allows the identification of the most significant risks and impacts, respecting the facilities characteristics, the geological conditions of the basin and the associated natural processes, assisting to propose measures that reduce the probability or the magnitude of their occurrence. Then, this analysis requires an understanding of the stages of the frameworks for Risk Assessment of CO2 storage streams in geological formations of the main international organizations, based on studies of the literature reviewed for these purposes. In fact, the risk management procedures are necessary to maximize the intended isolation and to minimize the effects of possible CO2 leakage. Finally, the results demonstrate a consistent relationship between the Risk Assessment and Management tool and its frameworks specificities for this activity.